True compass [large type] : a memoir - Kennedy, Edward M. (Edward Moore), 1932-2009 (Twelve Large Print, 2009)
In his revealing autobiography, Kennedy discusses his distinguished career, his family and personal relationships, and the tragedies that have befallen his family over the many years.